VEGF, BMP-7, MatrigelTM, Hyaluronic Acid, In Vitro Cultured Chondrocytes and Trephination for Healing of the Avascular Portion of the Meniscus. An Experimental Study in Sheep - Forriol, Francisco; Giuseppe Longo, Umile; Duart, Julio; Ripalda, Purification; Vaquero, Javier; Loppini, Mattia; Romeo, Giovanni; Campi, Stefano; S. Khan, Wasim; O. Muda, Andrea; Denaro, Vincenzo (Current Stem Cell Research & Therapy, 2015)
Objective: To evaluate the effects of VEGF, BMP-7, MatrigelTM, hyaluronic acid, in vitro cultured chondrocytes and trephination to promote and enhance the healing process of avascular meniscal tears in an animal model. Methods: A longitudinal tear was produced in the inner avascular part of the meniscus of 24 sheeps. Each tear was treated with trephination technique and suture. The animals were divided into 6 groups to receive a different treatment: control (I); VEGF, BMP-7, MatrigelTM, hyaluronic acid, in vitro cultured chondrocytes. At 8 weeks from surgery, meniscal samples were explanted and analyzed by histology, immunohistochemistry, and histomorphometry. Results: At the histological examination, Group IV and VI showed a partial closure of the meniscal lesion, whereas Group I, II, III, and V did not show any evidence of healing. In the group IV, the healed tissue represented the 22.95% of the lesion area. In the group VI, the healed tissue represented the 43.75% of the lesion area. Conclusions: Autologous chondrocytes and BMP-7 associated with trephination and suture techniques enhanced healing process of meniscal tears in the avascular inner third of the meniscus in ovine model.
Keywords: repair